Condiciones de trabajo y riesgos para la salud de los artesanos de la madera en Dzityá - Ancona Ricalde, Elda María; Castillo Burguete, María Teresa (Estudios de Antropología Biológica, 2013)
Results are presented for part of a research project carried out from 2006-2008 in Dzitya, Yucatan State, on artisanal woodworking, one of the main economic activities in the town. Of the 1 496 inhabitants (inegi 2005), 80 are wood artisans working in 22 workshops. We made a case study (Stake 1999) using participant observation to understand the activity and associated family and community dynamics, as well as interviews and data triangulation for confirmation. In this paper we analyze the artisans’ risk perception of their work, and its health consequences for them and their families. The artisans perceive their work as “high risk” since they use no protective measures against the noise, sharp implements, wood dust, lacquers, paints and varnishes they are exposed to. Family members are also at risk since they live next to the workshops.